2017
DOI: 10.1111/ijcs.12403
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the perceptions of Chinese consumers towards the country‐of‐origin of dairy products

Abstract: The dairy incident in 2008 influenced Chinese residents' attitudes towards domestic and foreign brands in the market. This paper highlights the strong consumer perceptions existing in the Chinese dairy market towards the country of origin of dairy products. Chinese residents generally believe dairy products from foreign countries are superior than those from China. A new theoretical framework is developed to explore the driving factors of country-of-effects and its corresponding impacts. Consumers' image of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 72 publications
(83 reference statements)
4
36
2
Order By: Relevance
“…In this study we choose to evaluate Chinese consumers' behavioral patterns regarding brand experience and brand relationship since Chinese consumers' experience with global brands is rapidly growing posing a significant market potential. Due to significant volumes of export and investment of foreign countries to China, millions of Chinese consumers have been exposed to global brands from various developed and emerging countries, showing numerous choices and preferences for global product consumption patterns (Yang, Ramsaran, & Wibowo, 2018). Further, China has become one of the largest markets for global brands with rapidly increasing consumers' purchasing power (Villar, Di Ai, & Segev, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this study we choose to evaluate Chinese consumers' behavioral patterns regarding brand experience and brand relationship since Chinese consumers' experience with global brands is rapidly growing posing a significant market potential. Due to significant volumes of export and investment of foreign countries to China, millions of Chinese consumers have been exposed to global brands from various developed and emerging countries, showing numerous choices and preferences for global product consumption patterns (Yang, Ramsaran, & Wibowo, 2018). Further, China has become one of the largest markets for global brands with rapidly increasing consumers' purchasing power (Villar, Di Ai, & Segev, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature often includes the country-of-origin as a major driving force behind not only consumer animosity, but also consumer ethnocentrism. However, other determinants also play an important role in consumers' reactions to product evaluations (Kucukemiroglu et al, 2006;Nes & Ghauri, 1998;Spillan et al, 2007;Yang, Ramsaran, & Wibowo, 2018;Yoo & Donthu, 2005). Whereas country-of-origin is an affective and cognitive aspect of the consumer decision-making process, consumer ethnocentrism is an affective and normative inclination to avoid purchasing foreign made products.…”
Section: T a B L E 1 Inclusion And Exclusion Criteriamentioning
confidence: 99%
“…Such instruments may include quality certifications from regulatory authorities, the reputation of the manufacturer brand, or the perceived quality based on the product origin, etc. (Caswell and Padberg, 1992; Loureiro and McCluskey, 2000; Aprile et al ., 2012; Xie et al ., 2016; Yang et al ., 2018; Wang et al ., 2019; Vuong and Khanh Giao, 2020).…”
mentioning
confidence: 99%
“…Evidence has shown that consumers exhibit different levels of preference for products from different countries or regions, COO labels have an effect on consumers' purchase intention, and consumers are often willing to pay a price premium for products that carry certain origin attributes (Maheswaran, 1994; Loureiro and McCluskey, 2000; Loureiro and Umberger, 2007; Diamantopoulos, et al ., 2011; Menapace, et al ., 2011; Aprile, et al ., 2012; Gao, et al ., 2014; Xie, et al ., 2016; Wang, et al ., 2019). Previous studies have shown that product origin exerts substantial influence on Chinese consumers' (especially first-time parents) evaluation and purchasing of formula, with imported products being preferred by a large proportion of consumers because of their high confidence in product quality and safety from developed Western countries (El-Benni, et al ., 2019; Gong and Jackson, 2013; Li, et al ., 2017; Kendall, et al ., 2018; Yang, et al ., 2018; Zhang, et al ., 2018). Country stereotypes, consumer ethnocentrism, product familiarity and experience, product involvement and some cultural value differences were found to drive the country-of-origin effects (Chattalas, et al ., 2008; Yang, et al ., 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation